Electrical and thermal properties of polyethylene/silver nanoparticle composites. Issue 5 (2nd April 2013) - Jouni, Mohammad; Boudenne, Abderrahim; Boiteux, Gisèle; Massardier, Valérie; Garnier, Bertrand; Serghei, Anatoli
Abstract The concentration dependence of specific heat, electrical and thermal conductivities of nanocomposites based on high‐density polyethylene (HDPE) filled with silver nanoparticles have been investigated. The composites filled with high filler content show high electrical and thermal conductivities. The dielectric relaxation spectroscopy was used to investigate the electrical properties in the studied systems. The scaling law of electrical percolation was used for an exact estimation of the percolation threshold (Pc). A low electrical percolation threshold was found in the investigated composites. The rule of mixture was sufficient for the prediction of the specific heat dependence of HDPE–Ag nanocomposites as a function of the weight filler content. The basic models of the thermal conductivity have a tendency to underestimate the measured values for the low and high filler concentrations. POLYM. COMPOS., 2013. © 2013 Society of Plastics Engineers POLYM. COMPOS., 2013. © 2013 Society of Plastics Engineers